2013
DOI: 10.1097/tp.0b013e31827e6ab3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antimouse CD52 Monoclonal Antibody on Graft’s γδ Intraepithelial Lymphocytes After Orthotopic Small Bowel Transplantation in Mice

Abstract: Alemtuzumab, a humanized CD52 monoclonal antibody (mAb), has been used for immune induction in clinical small bowel transplantation (SBT). However, the local impact of CD52 mAb on the transplanted intestine is not known. In this study, we investigated the effects of CD52 mAb on the intestinal intraepithelial lymphocytes (iIELs) in grafts using a murine orthotopic SBT model. The antimouse CD52 mAb was used as a surrogate antibody. Graft rejection was assessed by histopathologic analysis, iIELs were isolated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Lymphocyte ablation, using thymoglobulin or alemtuzumab (Campath‐1H), is performed within hours before organ transplantation with detectable levels of the monoclonal antibody detectable in circulation at the end of the first postoperative week. The effect of the induction therapy on donor passenger cells is not clearly known; however, a murine orthotopic small bowel transplantation model revealed that alemtuzumab significantly depleted donor T cells within the lamina propria and intraepithelial compartment of the transplanted graft . In this mouse model, both γδ and αβ T cells were reduced in the gut after treatment with alemtuzumab.…”
Section: Allografts With Endogenous Trm Cellsmentioning
confidence: 84%
See 1 more Smart Citation
“…Lymphocyte ablation, using thymoglobulin or alemtuzumab (Campath‐1H), is performed within hours before organ transplantation with detectable levels of the monoclonal antibody detectable in circulation at the end of the first postoperative week. The effect of the induction therapy on donor passenger cells is not clearly known; however, a murine orthotopic small bowel transplantation model revealed that alemtuzumab significantly depleted donor T cells within the lamina propria and intraepithelial compartment of the transplanted graft . In this mouse model, both γδ and αβ T cells were reduced in the gut after treatment with alemtuzumab.…”
Section: Allografts With Endogenous Trm Cellsmentioning
confidence: 84%
“…In this mouse model, both γδ and αβ T cells were reduced in the gut after treatment with alemtuzumab. At 2 weeks posttransplantation, most γδ TCR + cells within the intraepithelial compartment were of host origin along with significant repopulation by host‐derived ‐αβ T cells . Lymphocyte ablation might therefore cause a period of lymphopenia within the allograft (of gut Trm cells), or it may increase the kinetics of repopulation of the allograft.…”
Section: Allografts With Endogenous Trm Cellsmentioning
confidence: 99%
“…Again, γδ T cells produced a Th2-like cytokine phenotype through production of IL-4, IL-10 and TGFβ 159. Administration of the monoclonal antibody anti-CD52 (alemtuzumab) prominently depletes the donor-derived γδTCR + iEL compartment in a mouse model of small bowel transplantation 160…”
Section: Allograft Responsesmentioning
confidence: 99%